2017
DOI: 10.1093/mnras/stx1555
|View full text |Cite
|
Sign up to set email alerts
|

Rapid optical variations correlated with X-rays in the 2015 second outburst of V404 Cygni (GS 2023+338)

Abstract: We present optical multi-colour photometry of V404 Cyg during the outburst from December, 2015 to January, 2016 together with the simultaneous X-ray data. This outburst occurred less than 6 months after the previous outburst in June-July, 2015. These two outbursts in 2015 were of a slow rise and rapid decay-type and showed large-amplitude (∼2 mag) and short-term (∼10 min-3 hours) optical variations even at low luminosity (0.01-0.1L Edd ). We found correlated optical and X-ray variations in two ∼1 hour time int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
2
3
0
Order By: Relevance
“…In every case except the MDM lightcurve from June 21 we see CCFs dominated by a single clear peak slightly after zero lag. These are all relatively broad, although vary substantially in width, and peak at lags of 10-50 s. This overlaps the 22.5 s and 34.8 s lags reported in the 2015 December outburst (Kimura et al 2017(Kimura et al , 2018. On June 21, the very large X-ray flare which is relatively uncorrelated with optical behaviour on long timescales dominates the MDM CCF producing a general rise towards late times.…”
Section: X-ray/optical Lags and Reprocessingsupporting
confidence: 69%
See 1 more Smart Citation
“…In every case except the MDM lightcurve from June 21 we see CCFs dominated by a single clear peak slightly after zero lag. These are all relatively broad, although vary substantially in width, and peak at lags of 10-50 s. This overlaps the 22.5 s and 34.8 s lags reported in the 2015 December outburst (Kimura et al 2017(Kimura et al , 2018. On June 21, the very large X-ray flare which is relatively uncorrelated with optical behaviour on long timescales dominates the MDM CCF producing a general rise towards late times.…”
Section: X-ray/optical Lags and Reprocessingsupporting
confidence: 69%
“…8 to avoid compressing the outburst data, but we do find the extrapolation falls within about a factor of two of the quiescent accretion light. Kimura et al (2017) examined X-ray vs. optical correlations during the 2015 December outburst in a similar way, and found power-law indices of 0.25-0.29. These are based on much more limited time coverage than we have used, however, and sample a smaller dynamic range of luminosity.…”
Section: X-ray and Optical Flux Correlationsmentioning
confidence: 98%
“…The INTEGRAL and Swift spectra were compatible with a Comptonised continuum modified by a Compton-thick partial covering absorber [207]. Optical photometry [220] and spectroscopy, as well as monitoring in radio [334] also showed a behaviour comparable to what was observed in June, including similar, though less pronounced, P-Cyg optical lines and radio variability.…”
Section: The December 2015 Re-flaresupporting
confidence: 59%
“…This lag was interpreted as the delay between fluctuations generated in the hot corona around the BH, that propagate up to the relativistic jet base about 1000 R g away, which is responsible for part of the optical emission [e.g., 266]. The correlated 1-minute time scale optical lags correspond to the light travel time delays from the BH to the outer disc, were instead likely produced by the re-processing of the X-rays in the outer accretion disc, or by the illuminated binary companion [220,1,186].…”
Section: Rapid Multi-wavelength Variabilitymentioning
confidence: 99%
“…The most remarkable example is found on day 8, when observations deviate from the trend, having a higher optical emission than those observed in days 1-3 at similar X-ray fluxes. Studies on the X-ray to optical correlation during the 2015J outburst of V404 have revealed a non-trivial relationship, showing from null to 30 minutes lags when comparing flares in different epochs (e.g., Rodriguez et al 2015, Kimura et al 2017; see also Alfonso-Garzon et al 2018 in prep.). These lags may be responsible for the deviation from the trend in our lower time-resolution observations.…”
Section: X-ray-optical Flux Correlationmentioning
confidence: 99%